Bioarchaeology, Bioethics, and the Beothuk. Issue 1 (22nd November 2017) - Pullman, Daryl
ABSTRACT: The Beothuk of Newfoundland and Labrador have been extinct since the early nineteenth century, but skeletal remains of twelve Beothuk individuals are in storage at Memorial University in St. John's, Newfoundland, and those of another ten are in the archives of the Canadian Museum of History in Gatineau, Quebec. However, the best‐known and most widely discussed Beothuk remains reside in the stores of the National Museum of Scotland in Edinburgh. These are the skulls of Nonosabasut and his wife Demasduit, both of whom came to untimely ends through contact with European colonizers. In recent years, efforts have been made to repatriate these skulls to Newfoundland and Labrador. However, Canada has no equivalent legislation to the US NAGPRA, which provides direction with regard to "unaffiliated remains." Who then speaks for the Beothuk? This article explores some of the ethical and legal challenges associated with repatriating the remains of now‐extinct peoples, especially when those remains reside in a foreign territory. The ongoing ethical tension between the interests of science and those of justice are addressed, and a compromise solution is proposed. [ bioarchaeology, bioethics, repatriation, justice, Beothuk ]